2014
DOI: 10.4293/jsls.2014.00058
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Laparoscopic Gynecologic Surgery

Abstract: Background and Objectives:To analyze the frequency of complications during laparoscopic gynecologic surgery and identify associated risk factors.Methods:A descriptive observational study was performed between January 2000 and December 2012 and included all gynecologic laparoscopies performed at our center. Variables were recorded for patient characteristics, indication for surgery, length of hospital stay (in days), major and minor complications, and conversions to laparotomy. To identify risk factors and vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 22 publications
5
26
1
1
Order By: Relevance
“…In the present study, we observed that the rate of major complications after gynecological laparoscopic surgery in the total population was 2.85%, with a rate of 3.2% seen after surgery for malignant diseases. This is within the range reported in previously published studies [7,20,21]. The early identification of patients with complications would be undoubtedly of great clinical value because it would facilitate optimal timing of therapeutic interventions to minimize the sequelae of such complications, particularly major ones that require surgical intervention for correction with a significant threat to short-and long-term outcomes [22].…”
Section: Discussionsupporting
confidence: 72%
“…In the present study, we observed that the rate of major complications after gynecological laparoscopic surgery in the total population was 2.85%, with a rate of 3.2% seen after surgery for malignant diseases. This is within the range reported in previously published studies [7,20,21]. The early identification of patients with complications would be undoubtedly of great clinical value because it would facilitate optimal timing of therapeutic interventions to minimize the sequelae of such complications, particularly major ones that require surgical intervention for correction with a significant threat to short-and long-term outcomes [22].…”
Section: Discussionsupporting
confidence: 72%
“…Our standardised assessment of intra‐ and postoperative complications revealed no significant difference between groups; but given reported rates of complications following gynaecological surgeries, the sample size was too small to be able to draw definitive conclusions. Further studies with larger patient cohorts are needed to answer this question …”
Section: Discussionmentioning
confidence: 99%
“…Further studies with larger patient cohorts are needed to answer this question. 39,40 A major concern with LP laparoscopy is the potential reduction of surgical exposure, which might increase the technical difficulty of interventions and lead to higher complication rates. We cannot comment on this issue, as we did not assess surgeons' impressions of visualisation and technical difficulty.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Lower morbidity and mor-tality rate, less postoperative pain and improved postoperative recovery as well as shorter hospital stay and reduced costs are the main arguments in favor of this approach. It is associated with a low frequency of complications, but is a procedure that is not without risk (3,4). Some of the complications that can occur include lesions of bowel, blood vessels, urinary tract, air embolism, cardiac arrhythmia, abdominal wall and omental injuries (5).…”
Section: Introductionmentioning
confidence: 99%